Le « Code Michau » : la réformation selon le garde des Sceaux Michel de Marillac - Lauriane Kadlec (Les Dossiers du GRIHL)
The « Code Michau », the last General Ordonnance also known as « reforming », is mostly often viewed as one man’s masterpiece : the garde des Sceaux Michel de Marillac. It’s a collecting work that comes from reforming aspirations of the Estates-generals of 1614 and the two Assemblies of Notables of 1617 and 1626. This Ordonnance was written to address the two previous failures : the first one, the edict of july 1617 by the Garde des Sceaux Guillaume Du Vair, then, the reforming edict of justice of june 1627 by the Garde des Sceaux Michel de Marillac, which both failed to pass following the opposition of Parlement of Paris. The Lit of Justice of January 15 of 1629, gathered to register the Code in this Court, discredited definitively the Ordonnace presented by Marillac : the « Code Michau » was never registred – passed on the registration book – although a Lit of Justice was held. That is what has provoked the repelling of this text in the Provincial’s Parlements and created an extraordinary precedent.